Isolation and Genomic Analysis of Single Circulating Tumor Cell Using Human Telomerase Reverse Transcriptase and Desmoglein‐2. Issue 4 (17th January 2022) - Song, Jae Won; Suh, Jungyo; Lee, Seok Won; Yoo, Jung Ki; Lee, Uijeong; Han, Jang Hee; Kwak, Cheol; Kang, Minyong; Kim, Yi Rang; Jeong, Chang Wook; Choi, Jin Woo
Abstract: As epithelial cells in the circulation are considered to originate from the tumor, the epithelial cell adhesion molecule has been commonly used as a standard marker for circulating tumor cells (CTCs) isolation. However, it seems to disappear after the epithelial–mesenchymal transition that most cancer cells undergo for intravasation. Thus, more advanced techniques for CTC detection are needed to better understand the clinical significance of CTCs. A cancer cell‐specifically‐infecting or replicating virus that codes a fluorescent monitor gene can be a solution to efficiently detect CTCs. Thus, the authors designed an adenovirus to bind to desmoglein‐2, which is highly expressed in most cancer cells. A cancer‐specific human telomerase reverse transcriptase promoter is inserted to control a viral E1 region. The adenovirus is utilized to compare the number of CTCs from renal cell carcinoma and prostate cancer patients before and after surgery. The isolated two or three CTCs are eligible for whole genome sequencing. The genomic analysis proves the difference of variants between primary tumors and CTCs. Taken together, it is a fast and exact serial method for CTC isolation and the enriched genome sequencing may be used to determine the prognosis and as a point‐of‐care system for patients with cancer. Abstract : Based on the different expressions of desmoglein‐2 and hTERT between normal and cancer cells, recombinant adenovirus 5/3 is designed to be replicated and express GFP only in cancer cells. GFP‐positive circulating tumor cells (CTCs) are precisely isolated from patient blood samples. The subsequent whole genome sequencing about real single CTC suggests the numerous changes of CDS region compared with primary tumor.